A natural resource assessment of Chapungu Ranch, Save Valley Conservancy, Zimbabwe - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2013.